The possibility of effective using the conservative and the minimally invasive treatment methods at various stages of the Dupuytren disease - Ekaterina K. Ovchinnikova; Sergey I. Gilfanov (Клиническая практика)
A literature review is presented on the conservative and minimally invasive methods of treating the Dupuytren contracture. The investigators discuss both the methods implemented into clinical practice and those, which are currently at the stage of clinical and laboratory trials, including the minimally invasive methods, which can be used not only at the later stages, but also in cases of early manifestations of the disease. Among them there are the combined use of conservative methods, the radiation therapy, the injections of collagenase and steroids, the use of immunodepressive medicines and the needle aponeurotomy. These methods can be used at the earliest stages of the disease, however, the absence of proper evidence base often hinders their wide implementation. Up to the present moment, there is no commonly acknowledged approach to managing and treating the patients with early stage of the disease. The modern approach is focused on the invasive treatment of only later disease stages and of the severe contracture cases. This is why we would like to emphasize the potential of minimally invasive methods at the early stages of the Dupuytren disease, as well as the necessity of further research in this direction along with the importance of implementing such methods into everyday practice of the physicians.